Cultural tourism facilities in the context of the increased risk of terrorism: Young tourists from Lithuania and security measures - Žuromskaitė, Brigita; Nagaj, Rafał (Turyzm/Tourism, 2018)
In view of the events that have been taking place in recent years, tourism security issues have become a popular subject in academic research. Terrorism attacks in trendy tourism destinations have raised a significant question: how can the tourist be protected and provided with quality? The article presents an evaluation of the significance of ‘soft’ and ‘hard’ security measures used in cultural tourism facilities by young tourists from Lithuania. The research showed that young tourists belong to the group of ‘courageous’ travellers, but their bravery has a limit. Young people want to travel ‘without restrictions’, feeling free, but they also want to know that someone has taken care of their safety.